2011
DOI: 10.1128/aem.05007-11
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Genotypic Characteristics of Clostridium difficile in a Closed and Integrated Human and Swine Population

Abstract: Recently, an apparent rise in the number of cases attributed to community-acquired Clostridium difficile infection has led researchers to explore additional sources of infection. The finding of C. difficile in food animals and retail meat has raised concern about potential food-borne and occupational exposures. The objective of this study was to compare C. difficile isolated from a closed population of healthy individuals consisting of both humans and swine in order to investigate possible food safety and occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 49 publications
(66 reference statements)
0
14
0
Order By: Relevance
“…Toxinotypes V and O have also been reported in humans (8,26). The common occurrence of toxinotype V in the present study underscores a potential concern, as this type has been associated with community-associated disease and increasing prevalence in CDI in humans (6,21,26,27). Further investigation is necessary, as some recent reports have found toxinotype V in asymptomatic people (21), and others found that there was no association between virulence attributes and clinical outcomes (28).…”
Section: Discussionmentioning
confidence: 83%
“…Toxinotypes V and O have also been reported in humans (8,26). The common occurrence of toxinotype V in the present study underscores a potential concern, as this type has been associated with community-associated disease and increasing prevalence in CDI in humans (6,21,26,27). Further investigation is necessary, as some recent reports have found toxinotype V in asymptomatic people (21), and others found that there was no association between virulence attributes and clinical outcomes (28).…”
Section: Discussionmentioning
confidence: 83%
“…Moreover, a recent study reported that occupational exposure to pigs significantly increases the likelihood of humans being colonized by C. difficile. Furthermore, the same study demonstrated that the strains isolated from animals and their handlers had the same ribotype, suggesting transmission between species (NORMAN et al, 2011). Another fact that has attracted attention is the large increase in the isolation of one specific ribotype, known as 078, from humans living in the United States and England.…”
Section: Clostridium Difficile As a Zoonotic Agentmentioning
confidence: 88%
“…Recent studies have shown that isolates from human cases of pseudomembranous colitis caused by C. diffi cile are genetically similar to strains isolated from domestic animals, which suggest that this disease could be zoonotic (JHUNG et al, 2008;NORMAN et al, 2011 Ciência Rural, v.44, n.5, mai, 2014. of C. diffi cile strains in Brazil. Most current reports are not robust and are limited to human isolates.…”
Section: Introductionmentioning
confidence: 99%